Optimasi Usaha Mikro Pembuatan Keripik Pisang Aneka Rasa Dalam Upaya Peningkatan Ekonomi Kalurahan Ngargosari - Agus Juara; Nurul Umam; Khanafi Khanafi; Galih Khusni Mubarok; Ahmad Zimam Wafi; David Candra; Nuroh Fauziyah Da’at Arina; Fittisatil Chusna; Hikmtul Ulya; Arifah Nur Aini; Rahmawati Rahmawati (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2022)
The implementation of community service activities in the Gotakan Village of Kulon Progo is Ngargosari Village is one of the Kalurahan in Samigaluh District, Kulon Progo Regency with the majority of work as farmers. One of them is bananas which are widely available in the area. Bananas can be processed into various products and various processed foods such as banana chips. To increase the income of housewives through entrepreneurship. Banana chips in Ngargosari Village are very lacking, therefore this program aims to increase the knowledge of residents in the Ngargosari Village area by providing knowledge about good entrepreneurship in this way is expected to help housewives in a good mindset if one day they want to start opening a business someday. The method used is interviews and collaboration with villagers in increasing the income of housewives through the Aneka Rasa Banana Chips entrepreneur. The analysis used is a qualitative analysis whose interviews are analyzed to obtain data on knowledge about entrepreneurship. The results of the analysis show that the level of knowledge of residents about Banana Chips entrepreneurship is still quite low, the program being carried out is to disseminate information about increasing the income of housewives through Banana Chips entrepreneurship in Ngargosari Village and by conducting cooking demonstrations with local housewives in the form of food products originating from the village. It is hoped that bananas will later become a product that the people of Ngargosari Village are proud of.